2020
DOI: 10.1002/smtd.201900892
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Molecule Interaction of Peptides with a Biological Nanopore for Identification of Protease Activity

Abstract: The facile and sensitive detection of peptides is essential for drug screening, pathogen detection, and protein sequencing. There are still challenges for the real‐time single‐molecule sensing and detection of peptides due to their versatile shape, structure, and charges brought by amino acids. Nanopore sensing is an emerging technology for sensing of biomolecules including DNA, RNA, and proteins. In this study, the interaction between peptides of different lengths (N6–N10) and charges with an engineered Mycob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…Protein nanopore interface contains a variety of uncharged and charged amino acid residues, which contribute to multiple interactions with single analytes including electrostatic interactions, vdW interactions and hydrogen bonds [27][28][29][30]. Previous works verified that non-covalent interactions between the nanopore sensing interfaces and targets could be manipulated to support accurate distinction of peptides/proteins [23,31,32]. Recently, a study demonstrated theoretically and experimentally the possibility of non-covalent interactions between a nanopore and analytes in regulating the current blockages [33].…”
Section: Introductionmentioning
confidence: 99%
“…Protein nanopore interface contains a variety of uncharged and charged amino acid residues, which contribute to multiple interactions with single analytes including electrostatic interactions, vdW interactions and hydrogen bonds [27][28][29][30]. Previous works verified that non-covalent interactions between the nanopore sensing interfaces and targets could be manipulated to support accurate distinction of peptides/proteins [23,31,32]. Recently, a study demonstrated theoretically and experimentally the possibility of non-covalent interactions between a nanopore and analytes in regulating the current blockages [33].…”
Section: Introductionmentioning
confidence: 99%
“…[50] During the last decade,n umerous efforts with biological nanopores have been invested into peptide and protein sensing,i ncluding conformation/structure characterization, [51][52][53][54][55][56] variant recognition, [24,26,27,[57][58][59][60][61][62][63] interaction investigation, [64][65][66][67][68][69] and protein kinase exploration. [70][71][72][73][74] However, despite all the present achievements in proteomic analysis, there is still along way toward SMPS.This minireview focuses on recent progress in biological nanopore approach for SMPS, and attempts to provide acomprehensive overview of current experimental efforts and strategies for overcoming major hurdles of NPS.F inally,w ec lose it with our insights and perspectives on future developments in the field of NPS.…”
Section: Introductionmentioning
confidence: 99%
“…Each data point was estimated from the reported longest residencesofpeptides.R elated references were shown in the right parentheses, where asterisk indicate the capability for identification of single AA difference. Compared to the results obtained with wild-type (WT) biological nanopores(open circles),[25,28,29,44,48,54,66,67,69,73,[75][76][77][78][79][80][81] translocation velocities of peptides have been remarkably reduced by designingmutant nanopores( red solid circles),[30,70,82,83] introducing dipolar-like peptide structures (orange solid triangles),[57,58,[84][85][86] and optimizing solution conditions, such as temperatures (blue solid diamonds)[87,88] and pH (violet solid pentagons) [89]. Ideal velocitiesinsuggested region were coloured in light blue.…”
mentioning
confidence: 99%
“…Besides, single molecule sensing of proteins is another promising application of nanopore technology [18]. Various nanopore proteins have been used for detection of peptides [19,20], protein biomarkers [21][22][23][24][25], post-translational modifications [26], protein unfolding [27], and protein conformation [28]. Recently, Ouldali et al reported the electrical recognition of the 20 proteinogenic amino acids [29], paving the way to nanopore protein sequencing.…”
Section: Introductionmentioning
confidence: 99%